Effect of folA gene in human breast milk-derived Limosilactobacillus reuteri on its folate biosynthesis - Jiang, Yu; Li, Xianping; Zhang, Wei; Ji, Yadong; Yang, Kai; Liu, Lu; Zhang, Minghui; Qiao, Weicang; Zhao, Junying; Du, Mengjing; Fan, Xiaofei; Dang, Xingfen; et al. (Frontiers in Microbiology, 2024)
Folate supplementation is crucial for the human body, and the chemically synthesized folic acid might have undesirable side e ffects. The use of molecular breeding methods to modify the genes related to the biosynthesis of folate by probiotics to increase folate production is cur rently a focus of research. In this study, the folate-producing strain of Limosilactobacillus reuteri B1-28 was isolated from human breast milk, and the difference between B1-28 and folA gene deletion strain ΔFolA was investigated by phenotyping, in vitro probiotic evaluation, metabolism and transcriptome analysis. The results showed that the folate producted by the ΔFolA was 2-3 folds that of the B1-28. Scanning electron microscope showed that ΔFolA had rougher surface, and the acid-producing capacity (P = 0.0008) and adhesion properties (P = 0.0096) were significantly enhanced than B1-28. Transcriptomic analysis revealed that differentially expressed genes were mainly involved in three pathways, among which the biosynthesis of ribosome and aminoacyl-tRNA occurred in the key metabolic pathways. Metabolomics analysis showed that folA affected 5 metabolic pathways, involving 89 different metabolites. In conclusion, the editing of a key gene of folA in folate biosynthesis pathway provides a feasible pathway to improve folate biosynthesis in breast milk-derived probiotics.